2018
DOI: 10.1177/1084822318793882
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Medicare Home Health Patients by Admission Source

Abstract: Unlike other post-acute care settings, a large and growing share of Medicare Fee-For-Service patients are admitted to home health without a prior hospitalization or facility-based post-acute stay. Differences in home health patients by admission source have implications for standardizing measurement, and potentially payment, across post-acute care settings. We examined home health patients' demographic, health, and utilization patterns when stratified by their admission source. We found that community-admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Current HH reimbursement structures incentivize HH agencies to limit the number of visits provided; as a result, HH staff report difficulty addressing underlying social needs due to agency policies limiting visit frequency and duration 33 . Study findings echo previous research in demonstrating that community‐referred HH patients are more likely to have cognitive impairment and/or be at risk for incident ADRD diagnosis 14,34 . This highlights the need for revisions to the current Medicare HH payment system, which reimburses post‐acute episodes at a higher level than community‐entry episodes, to create reimbursement parity between referral sources for those with cognitive impairment, thus supporting continued access and quality of care 18,19,35 …”
Section: Discussionsupporting
confidence: 48%
“…Current HH reimbursement structures incentivize HH agencies to limit the number of visits provided; as a result, HH staff report difficulty addressing underlying social needs due to agency policies limiting visit frequency and duration 33 . Study findings echo previous research in demonstrating that community‐referred HH patients are more likely to have cognitive impairment and/or be at risk for incident ADRD diagnosis 14,34 . This highlights the need for revisions to the current Medicare HH payment system, which reimburses post‐acute episodes at a higher level than community‐entry episodes, to create reimbursement parity between referral sources for those with cognitive impairment, thus supporting continued access and quality of care 18,19,35 …”
Section: Discussionsupporting
confidence: 48%
“…Mroz et al ( 14 ) found that community-admitted patients were significantly more likely to be nonwhite, Medicaid-enrolled, and have cognitive impairment; however, the sample was restricted to residents of rural areas. Fout et al ( 15 ) found that a greater proportion of community-admitted patients had cognitive impairment and were Medicaid-enrolled, and Wysocki and Cheh ( 6 ) found that community-admitted patients were significantly more likely to be Medicaid-enrolled and live in a state with high levels of home health provider fraud/abuse. However, none of these studies examined contextual factors measured before the home health episode or examined differences in patient characteristics by both referral source and number of episodes.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Our study fills two remaining gaps in the available literature regarding variation in home health patient characteristics between those with versus without an immediately preceding hospitalization. First, although contextual factors, such as availability of family caregivers, may affect home health care utilization and represent another facet of social vulnerability, all previous work has been restricted to measures gathered during the home health episode, missing potentially valuable information about patients’ social contexts ( 6 , 14 , 15 ). We draw on a unique analytic data set that links a nationally representative survey with comprehensive information on individual health, functional disability, and caregiver support before home health, to patient assessments conducted by home health clinicians during the episode of care and Medicare claims.…”
Section: Background and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given emerging research demonstrating that a growing number of family caregivers are assisting with medically oriented tasks, 16,22 we also include clinician reports of the presence of pressure ulcers or wounds from the OASIS. Finally, in response to growing awareness of differences in characteristics of patients referred to home health from the community versus those referred following an inpatient stay, 23,24 we incorporate a measure of whether the home health episode is postacute. If the home health episode occurs within 14 days of inpatient acute or postacute care, we define this as a postacute episode.…”
Section: Methodsmentioning
confidence: 99%